The effects of intracerebroventricularly applied ghrelin on thymocytes and thymic architecture in rats of different ages - Todorović, Jovana S.; Terzić Šupić, Zorica J.; Mazić, Sanja D.; Suzić Lazić, Jelena M.; Žikić, Dejan T.; Nešić, Dejan M. (Archives of Biological Sciences, 2020)
Paper description: The growth hormone secretagogue receptor R1a, the receptor for ghrelin, is expressed in immune cells. The influence of intracerebroventricularly administered ghrelin (1 μg/day/rat for 5 days) to rats of different ages (peripubertal (5 weeks), young (2 months) and middle-aged (6 months; n=10 per group), on thymus mass and thymic architecture was examined. Intracerebroventricular application of ghrelin postponed thymic atrophy: the average weights of the thymuses were significantly higher in the ghrelin groups; ghrelin positively influenced the number of thymocytes and thymic structure. Our results point to a stimulatory effect of ghrelin on thymic size and function. Abstract: Ghrelin positively influences the total number of thymocytes and size of the thymus in 14-, 20- and 24-month-old rats. We examined the effect of centrally-applied ghrelin on thymus weight and structure in Wistar rats of different ages. The study included 30 male Wistar rats of three age groups: peripubertal (5-week-old rats), young (2 months) and adult (6 months). The animals of each age group were divided into control and experimental groups that were administered intracerebroventricularly (ICV) 1 μg ghrelin/5 μL saline daily for five consecutive days. Following treatment, the thymuses were isolated, weighed and processed for stereological analysis by the point-counting method. The average weights of the thymuses were significantly higher in the ghrelin groups with respect to control rats (5 weeks: 444.90±18.03 vs 365.00±18.63; 2 months: 354.30±13.77 vs 257.00±9.60; 6 months: 365.00±15.90 vs 225.00±7.03, p<0.01). The absolute volume of lymphoid tissue was significantly higher in the ghrelin groups (5 weeks: 392.85±16.94 vs 294.48±33.37; 2 months: 309.30±12.10 vs 216.62±10.72; 6 months: 222.70±11.41 vs. 114.33±16.48, p<0.01). Ghrelin treatment restored thymic structure by increasing medullary cellularity, improving thymic medullary architecture and providing a clearer delineation between the cortex and medulla. This study shows the positive effects of centrally applied ghrelin on suppression of thymus atrophy, its weight and architecture. https://doi.org/10.2298/ABS200416020T Received: April 16, 2020; Revised: May 1, 2020; Accepted: May 3, 2020; Published online: May 11, 2020 How to cite this article: Todorović JS, Terzić Šupić ZJ, Mazić SD, Suzić Lazić JM, Žikić DD, Nešić DM. The effects of intracerebroventricularly applied ghrelin on thymocytes and thymic architecture in rats of different ages. Arch Biol Sci. 2020;72(2):265-70.